FRI0538 Structural effects of intra-articular sprifermin in symptomatic radiographic knee osteoarthritis: a post-hoc analysis of cartilage and non-cartilaginous tissue alterations of the 2-year data from a 5-year randomised, placebo-controlled, phase ii study. (12th June 2018) - Roemer, F.; Kraines, J.; Aydemir, A.; Wax, S.; Crema, M.; Hochberg, M.; Guermazi, A.
Abstract : Background: Sprifermin, a recombinant human fibroblast growth factor 18, is currently being investigated as a potential disease-modifying osteoarthritis (OA) drug. Recently, a dose-dependent increase in femorotibial cartilage thickness, as well as medial and lateral compartment cartilage, over two years was reported 1 . Objectives: The aim of this post-hoc analysis is to evaluate potential effects of sprifermin on additional structure endpoints, based on semi-quantitative MRI assessment over 24 months. Methods: Patients aged 40–85 years with symptomatic radiographic knee OA, KLG 2 or 3, and medial mJSW ≥2.5 mm in the target knee were randomised (1:1:1:1:1) to receive double-blinded placebo or sprifermin (30 µg or 100 µg), administered as 3 weekly intra-articular injections in cycles every 6 or 12 months. 1.5T or 3T MRIs were acquired at baseline, 6, 12, 18 and 24 month follow-up visits using a standard protocol (ClinicalTrials.gov identifier: NCT01033994 ). MRIs were read using the Whole-Organ Magnetic Resonance Imaging Score (WORMS) system (time points of baseline, 12 and 24 months) by three trained musculoskeletal radiologists. Analyses of all sprifermin and placebo arms included multiple MRI-defined osteoarthritis features and multi-dimensional assessments: (a) delta-subregional approach (the difference in the number of subregions with worsening as compared to improvement) and (b) delta-sum approach (absolute scores of all subregions). Analyses were performed on a whole knee level and separately for medial, lateral, and patellofemoral compartments. To test for potential dose-response effects, Jonckheere-Terpstra (asymptotic) test was used. P-values were not adjusted for multiple testing. Results: 549 patients were included. Dose-dependent treatment effect on cartilage morphology (i.e., less cartilage damage) was observed for the entire knee from baseline to 24 months using both delta sum and delta subregion approaches (table 1). For bone marrow lesions (BMLs), a dose-dependent treatment effect (improvement of BMLs) was observed from baseline to 24 months for the patello-femoral joint using both delta sum and delta subregion approaches but not the other compartments (table 2). No significant effects were seen for baseline to 24 month changes in Hoffa-synovitis, effusion-synovitis, menisci, or osteophytes. Conclusions: This post-hoc analysis indicates that sprifermin has a positive effect on cartilage morphology, in addition to the previously reported effect on cartilage thickness. Sprifermin was also associated with BML improvement in the patello-femoral joint. There were no significant effects associated with sprifermin on other joint tissues assessed, and no safety concerns raised. Reference: [1] Hochberg MC, et al. Efficacy and Safety of Intra-Articular Sprifermin in Symptomatic Radiographic Knee Osteoarthritis: Results of the 2-Year Primary Analysis from a 5-Year Randomised, Placebo-Controlled, Phase II Study [abstract]. Arthritis Rheumatol 2017;69(suppl 10). Disclosure of Interest: F. Roemer Shareholder of: Boston Imaging Core Lab (BICL), LLC., J. Kraines Employee of: EMD Serono, A. Aydemir Employee of: EMD Serono, S. Wax Employee of: EMD Serono, M. Crema Shareholder of: Boston Imaging Core Lab (BICL), LLC., M. Hochberg Consultant for: Bioiberica SA, Bristol Myers Squibb, EMD Serono, Galapagos, IBSA Biotechniq SA, Novartis Pharma AG, Pfizer Inc., Plexxikon, Samumed LLC, Theralogix LLC and TissueGene Inc, A. Guermazi Shareholder of: Boston Imaging Core Lab (BICL), LLC., Consultant for: to MerckSerono, TissueGene, GE, Pfizer, OrthoTrophix, AstraZeneca and Sanofi